Salmonellosis Outbreak Traced to Playground Sand, Australia, 2007–2009 - Staff, Michael (Centers for Disease Control and Prevention, 2012)
A community outbreak of gastroenteritis in Australia during 2007–2009 was caused by ingestion of playground sand contaminated with Salmonella enterica Paratyphi B, variant Java. The bacterium was also isolated from local wildlife. Findings support consideration of nonfood sources during salmonellosis outbreak investigations and indicate transmission through the animal–human interface.